Are the Health Services for Children with Special Health Care Needs Met Through School Services? - Schillo, Rachel A. (My University, 2014)
The Maternal and Child Health Bureau recognizes children with special health care needs (CSHCN) as "those with chronic physical, developmental, behavioral, or emotional conditions that require health and related services of a type or amount beyond that required of children generally" (Kuhlthau, Bloom, Van Cleave, Knapp, Romm, Klatka... Perrin, 2011, p.136). These children may need medication, medical care, mental or educational services, or special therapy in order to maintain functionality (Houtrow, Okumura, Hilton, & Rehm, 2011). A significant number of CSHCN attend school daily who require additional health support (DurRant, Gibbons, Poole, Suessmann, & Wyckoff, 2010). Federal law mandates schools to adapt their services to provide equal opportunity for the student body including CSHCN, but many schools struggle to adapt programs due to cost of personnel and resources (Murphy & Carbone, 2008). When school services are not fully available to CSHCN, they are more likely to have unfavorable outcomes in school such as repeating grade, lack of engagement, and increased absences (Reuben & Pastor, 2013). To ensure that the health needs of children with disabilities are met adequately at schools, it is important to understand how schools provide comprehensive services for them (Reuben & Pastor, 2013). / This honors project was conducted in rural eastern North Carolina at a school-based health center in collaboration with a school nurse in Wayne County. The purpose of this project was to examine the health services available to the 81 CSHCN at Brogden Middle School and determine barriers to available health services. The objectives of this project were 1) to interview 4-5 key informants in the public school who have close contact with CSHCN by Feb 11, 2014 and 2) identify programs and services most utilized by CSHCN at this public school by Feb 17, 2014. Public health interventions used in this project were advocacy and policy enforcement. Written recommendations based on the findings will be provided to the Director of the school-based health center, school nurse, and key teachers to improve services for CHSCN in this school. /
Keywords: Children with special health care needs; Health services; School services